2010
DOI: 10.1007/s11207-010-9543-2
|View full text |Cite
|
Sign up to set email alerts
|

Faraday Rotation Response to Coronal Mass Ejection Structure

Abstract: We present the results from modeling the coronal mass ejection (CME) properties that have an effect on the Faraday rotation (FR) signatures that may be measured with an imaging radio antenna array such as the Murchison Widefield Array (MWA). These include the magnetic flux rope orientation, handedness, magnetic-field magnitude, velocity, radius, expansion rate, electron density, and the presence of a shock/sheath region. We find that simultaneous multiple radio source observations (FR imaging) can be used to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…In these analyses, various portions of the CME response were measured (the shock sheath, the erupting prominence material), and compared with equivalent portions of the CME in coronagraph observations. In the analysis of the 28 October 2003 CME, showed that the prominence material of the CME is elongated in the direction of the Earth, and approximates the loop-like magnetic field structure measured in-situ at Earth for this event (Jensen et al 2010;Jackson et al 2011a). The SMEI reconstructions agreed well with in situ density measurements at Earth and STEREO (e.g., Jackson et al , 2010bJackson et al , 2012.…”
Section: Three-dimensional Reconstruction Of Cmes and Resultsmentioning
confidence: 52%
“…In these analyses, various portions of the CME response were measured (the shock sheath, the erupting prominence material), and compared with equivalent portions of the CME in coronagraph observations. In the analysis of the 28 October 2003 CME, showed that the prominence material of the CME is elongated in the direction of the Earth, and approximates the loop-like magnetic field structure measured in-situ at Earth for this event (Jensen et al 2010;Jackson et al 2011a). The SMEI reconstructions agreed well with in situ density measurements at Earth and STEREO (e.g., Jackson et al , 2010bJackson et al , 2012.…”
Section: Three-dimensional Reconstruction Of Cmes and Resultsmentioning
confidence: 52%
“…to determine the distance of the heliospheric interstellar boundary, or the dynamic solar wind pressure at Mars, and its effect on the Martian magnetosphere . In combination with Faraday rotation (FR) observations, bulk densities allow the remote determination of heliospheric vector magnetic field components globally (Jensen et al, 2010). This combination of bulk density measurements combined with FR observations planned from radio arrays such as the Murchison Widefield Array (MWA) or the LOw Frequency ARray (LOFAR) now under construction may usher in a whole new remote-sensing capability.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the magnetic field perturbation of the 1983 Alfven perturbations inferred that the efflux energy at 4 solar radii was at least 6脳10 19 W. It approximately accounts for 20% of the wave energy required to accelerate the solar wind (Jensen & Russell 2009). Further, the Faraday rotation observations of CME/ICMEs have demonstrated the usefulness of determining the critical parameters, such as the orientation and radius of a flux cylinder in the interplanetary space (Jensen et al 2010).…”
Section: Turbulence In the Fast/slow Solar Wind Flowsmentioning
confidence: 99%